(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda is the Upaveda of Atharvaveda, the ancient literature which gave us the knowledge of healthier life. The absolute aim of Ayurveda is to maintain the health of a healthier person and diagnose and treat the diseased person. Ayurveda has the ability to treat many chronic diseases that are untreatable in modern medicine, it has got some very preventive and curative tools to treat the diseases, but unfortunately, due to the lack of scientific validation in various concepts, this precious gift from our ancestors is trailing. In a nutshell, Ayurveda gives human a healthy life with proven methods of medical treatment. The ancient methods of treatment are very effective and relevant in present time also. Hence, evidence-based research is highly needed for global recognition and acceptance of Ayurveda, which needs further advancements in the research methodology.